Anti-diabetic Activity of Tabat Barito Leafs (Ficus deltoidea, Jack) Extract in Rats - Heru Agus Cahyanto; Nana Supriyatna (Biopropal Industri, 2013)
Tabat barito (Ficus deltoidea, Jack) leaf is believed could be used to treat diabetes. But more scientific data are needed. The aim of this study is to investigate  antidiabetic activity of  Tabat Barito extract by glucose tolerance method. The treatment was given in three doses (50, 100, and 200 mg/kg BW) and two controls using aquoeus and glibenklamid.  Tabat barito extract was obtained by maceration and made into dry extract with addition of starch. The result showed that chemical compound of the ethanol extract were fenolic and saponin. The extract showed effects in lowering blood sugar levels with glucose tolerance methods at 30 to 60 minutes. Blood glucose levels of mice treated with the extract extract ranged between 132.60 to 258.00 mg/dL , glibenklamide ranged from 130.20 to 144.60 mg/dL, and aqua ranged between 227.60 to 260.20 mg/dL. The percentage decrease in blood sugar levels compared to controls is 32.54%.